2023
DOI: 10.1155/2023/3599501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Ratios of Mentha spicata Aqueous Solution Based on a Biosolvent on the Synthesis of AgNPs for Inhibiting Bacteria

Abstract: Our work was devoted to studying the effect of different concentrations of Mentha spicata aqueous extract on the green synthesis of silver nanoparticles (AgNPs) in order to obtain the most effective of these concentrations for bacteria inhibitory activity. Different concentrations of the aqueous M. spicata extract (0.25, 0.50, 0.75, and 1.00 mM) were used as biological solvent to synthesize AgNPs by means of the reduction method. The crystal structure and morphology of the NPs were characterized UV–vis spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In the UV-Vis Spectra of MAgNPs showed peaks at 454, 353, 343, and 340nm. Although these peaks were different in the silver nanoparticles synthesized with M. spicata (Qaeed et al, 2023), their work revealed peaks at 455, 458, 459, and 479nm. It is suspected that electrons move very freely because the valence bond is close to the conduction band, increasing the surface plasmon resonance (SPR) absorption, which causes the MAgNPs electrons to resonantly oscillate with the incident light.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the UV-Vis Spectra of MAgNPs showed peaks at 454, 353, 343, and 340nm. Although these peaks were different in the silver nanoparticles synthesized with M. spicata (Qaeed et al, 2023), their work revealed peaks at 455, 458, 459, and 479nm. It is suspected that electrons move very freely because the valence bond is close to the conduction band, increasing the surface plasmon resonance (SPR) absorption, which causes the MAgNPs electrons to resonantly oscillate with the incident light.…”
Section: Discussionmentioning
confidence: 89%
“…3). The UV spectra of the MAgNPs show a gradient of increasing absorption, this is due to the varying sizes and shapes of the particles as well as the availability of phytochemical compounds in the extract (Qaeed et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In the modern era, a multitude of research studies have extensively documented the remarkable efficacy of plant extracts in combating pathogenic bacteria that pose a threat to human health. These investigations have shed light on the potent antibacterial properties exhibited by diverse plant extracts [ 21 , 22 , 23 ]. In our investigation, we conducted both in silico and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the colours on these fabrics exhibited modest resistance to colour staining when wet, with minimal to no colour bleeding or transfer to other surfaces. Conversely, the sample printed with stannous chloride and ferrous sulfate mordants exhibited poor wet crock fastness with a rating of 2, suggesting that the colour on the fabric displayed limited resistance to staining when exposed to moisture, resulting in noticeable colour transfer to other surfaces [22] .…”
Section: Crock Fastnessmentioning
confidence: 99%